2019
DOI: 10.1093/cvr/cvz305
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics links oxidized phosphatidylcholines and coronary arteritis in Kawasaki disease

Abstract: Aims Coronary arteritis is a life-threatening complication that may arise in the acute stage of Kawasaki disease (KD), the leading cause of systemic vasculitis in childhood. Various microorganisms and molecular pathogens have been reported to cause KD. However, little is known about the key molecules that contribute to the development of coronary arteritis in KD. Methods and results To identify causative molecules for coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…These data implicate the pathogenic role of atherogenic signals in KD. This suggests that the triggering of the innate response begins not only through the PAMPs or damage-associated molecular patterns (DAMPs) (26) but also from the activation of multiple pathways in a variety of cell types (27).…”
Section: Discussionmentioning
confidence: 99%
“…These data implicate the pathogenic role of atherogenic signals in KD. This suggests that the triggering of the innate response begins not only through the PAMPs or damage-associated molecular patterns (DAMPs) (26) but also from the activation of multiple pathways in a variety of cell types (27).…”
Section: Discussionmentioning
confidence: 99%
“…70,71 Oxidised phospholipids and LDLs, as DAMPs, modify the epigenetic status of monocytes and vascular cells, facilitate memory responses and boost inflammation. 72 Since oxidised phospholipids and LDLs are elevated during the acute phase of KD, 58 we hypothesise that such DAMPs may reprogramme the cellular metabolism and boost hyperinflammation of innate immune cells and vascular cells in patients with KD during its onset and recurrence. 67,68 Furthermore, the clinical and laboratory data have shown that serum IL-1b levels increase and IL-1 signalling is upregulated in KD.…”
Section: Pathophysiology Of Kdmentioning
confidence: 99%
“…107 In a subsequent high-resolution LC-MS-based lipidomic analysis, we confirmed that the KD-associated molecules possessed structures similar to those found in biofilm extracts from Y. pseudotuberculosis. 58…”
Section: Identification Of Possible Pamps In Kd Seramentioning
confidence: 99%
See 2 more Smart Citations